Factors affecting students’ academic performance: a case study at a public university in Negeri Sembilan / Nurfahimah Mohd Nor, Nur Anis Nabilah Ahmad Zamri and Siti Sarah Januri - Mohd Nor, Nurfahimah; Ahmad Zamri, Nur Anis Nabilah; Januri, Siti Sarah (Universiti Teknologi MARA, Negeri Sembilan, 2023)
A student is someone who attends school or another educational institution to learn, acquire skills, and find a job. A student is anybody who intensively studies a subject to master it for a practical purpose. Student success is measured by academic topics. Continuous assessment, CGPA, and standardized exam scores are used by educators to evaluate student performance. Academic performance contributes to academic achievement. Socioeconomic position, student personality and motivation, and peer and family support affect academic success (Maguin and Loeber, 1996). Tomul and Celik (2009) found various family factors affect academic performance, while Lin and Han (2017) stated lower-income parents are busy and don't expect much from their kids, and they may also prioritize food above schooling. Usaini and Abubakar (2015) reported that parents with formal jobs used their monthly salaries to buy books and stationery for their children. Their steady income allows them to invest heavily in their children's education. Professionals provide their children with learning materials, which helps them succeed in school (Machebe, Ezegbe, & Onuoha, 2017). Youth growth depends on academic performance. Young individuals entering the workforce must have a solid foundation of education and, in many cases, specialized skills due to job specialization. Consequently, the purpose of the study is to establish the primary elements that impact students’ academic performance in terms of gender, age, parental occupation, parental education, parental income, and opinion and to identify the relationship between gender and academic performance.